Some Recurrence Relations and Hilbert Series of Right-Angled Affine Artin Monoid M(D~n∞) - Young Chel Kuwn; Zaffar Iqbal; Abdul Rauf Nizami; Mobeen Munir; Sana Riaz; Shin Min Kang (Journal of Function Spaces)
We find the Hilbert series of the right-angled affine Artin monoid M(D~n∞). We also discuss its recurrence relation and the growth rate.